Integrating psychosocial health into disaster risk management: Insights from COVID-19 in Durán, Ecuador - Mercy J. Borbor-Cordova; Madison Searles; Heydi Roa-López; María del Pilar Cornejo-Rodriguez; Katty Castillo; Andrea Orellana-Manzano; Christina D. Campagna (PLoS ONE, 2026)
The COVID-19 pandemic and intensifying climate-related disasters have highlighted the necessity of integrating psychosocial health and disaster risk management strategies. In the post-pandemic context, it is important to understand the psychosocial vulnerability factors that exacerbate stress and depression in order to inform interventions that enhance resilience during disaster preparedness and recovery efforts. Self-reported stress and depression were evaluated to assess risk and protective factors using questionnaires that were completed by 340 out of 446 participants in Durán, Ecuador in 2021. Considering social vulnerability factors of exposure, sensitivity and adaptive capacity at individual and urban levels, this study applied Kendall’s tau and odds ratio analyses to explore associations between stress and depression, identifying risks and protective factors within the sample population. Women (68.5%) self-reported to be vulnerable to moderate stress (67.8%) and mild depression (29.6%). There was a positive association between stress and depression levels (0.42, p: < 0.02 ). Odds ratio indicated adults experienced moderately severe stress, while those who were in domestic partnership had a 20% reduced risk of stress. Participants living in collective housing and rooms in tenement housing and apartments were more likely to experience higher levels of stress. Depression levels are associated with chronic illnesses (p < 0.02), residing in areas lacking paved roads (p < 0.005 ), without access to water (p < 0.036 ), and without COVID-19 vaccination ( p < 0.043 ). The Duran study revealed the complex nature of psychosocial health, shaped by individual vulnerabilities, deficient urban infrastructure, and limited capacities of city systems. In the long-term recovery process, the integration of mental health and disaster risk management (DRM) would focus on community-engagement for preparedness, equitable access to health/mental services, inclusive urban planning, and partnerships intervention to enhance community adaptive capacity to improve resilience and promote sustainable recovery. In line with the Sendai Framework for disaster risk reduction (DRR), humanitarian emergencies, climate and health crises, and compound risks offer critical opportunities to advance resilience in urban and health systems by addressing structural vulnerabilities, enhancing interinstitutional coordination, and integrating mental and psychosocial health into disaster risk reduction and management strategies.